Lambert Eaton Myasthenic Syndrome diagnosed following prolonged neuromuscular blockade: beware the patient with weak legs. Issue 2 (28th August 2016) - Linton, Fiona; Skubula, Alexandra; Ibrahim, Heba; Jee, Richard
Summary: We present the case of a patient who had a tonsillar biopsy as a day case and developed prolonged neuromuscular blockade. He was diagnosed with Lambert Eaton Myasthenic Syndrome (LEMS) and a subsequent biopsy confirmed mixed small and non‐small cell lung cancer. This case reinforces the importance of neuromuscular monitoring and investigating episodes of prolonged neuromuscular blockade. It also highlights the significance of patients who complain of lower limb weakness during their anaesthetic pre‐assessment and the requirement for further evaluation.